Nonlinear black-box identification of distillation column models - design variable selection for model performance enhancement - Ling, Wei-Ming; Rivera, Daniel E. (Zielona Góra: Uniwersytet Zielonogórski)
Conventional linear system identification techniques fail to capture the strong nonlinearity characteristic of distillation processes. On the other hand, general theories to guide selection of design variables in nonlinear system identification methods, such as the model structure selection, are lacking. In this paper, using the results of a binary distillation column simulation as a basis, problems relating to the proper selection of model structure and input perturbation design for nonlinear system identification are investigated systematically.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka